AKURASI POSISI GUNUNG SALAK SEBAGAI ARAH KIBLAT BAGI MASYARAKAT CIGOMBONG BOGOR PERSPEKTIF ILMU FALAK DAN FIKIH - Asathin, Muhamad Wildan; Kusdiyana, Kusdiyana; Bustomi, Ilham (Institut Agama Islam Negeri (IAIN) Syekh Nurjati Cirebon, 2025)
Muslims are commanded to worship, including prayer. In performing prayer, there are rules that have been determined and must be fulfilled, namely pillars and conditions. Facing the Qibla is one of the valid requirements in prayer, the Qibla is the closest direction to the Baitullah (Kaaba). For people who live close to the Kaaba, facing the Qibla is not a problem, but sometimes it can be a problem for people who live far from the Kaaba. One of them in Indonesia, precisely in Cigombong District, Bogor Regency, there is a unique phenomenon in the form of local wisdom regarding the direction of the Qibla, the community has a belief in Mount Salak as a benchmark for the direction of the Qibla. The formulation of the problem in this study is